Transjugular intrahepatic portosystemic shunt for the management of acute variceal hemorrhage - Loffroy, Romaric (Baishideng Publishing Group Co., Limited, 2013)
Acute variceal hemorrhage, a life-threatening condition that requires a multidisciplinary approach for effective therapy, is defined as visible bleeding from an esophageal or gastric varix at the time of endoscopy, the presence of large esophageal varices with recent stigmata of bleeding, or fresh blood visible in the stomach with no other source of bleeding identified. Transfusion of blood products, pharmacological treatments and early endoscopic therapy are often effective; however, if primary hemostasis cannot be obtained or if uncontrollable early rebleeding occurs, transjugular intrahepatic portosystemic shunt (TIPS) is recommended as rescue treatment. The TIPS represents a major advance in the treatment of complications of portal hypertension. Acute variceal hemorrhage that is poorly controlled with endoscopic therapy is generally well controlled with TIPS, which has a 90% to 100% success rate. However, TIPS is associated with a mortality of 30% to 50% in such a setting. Emergency TIPS should be considered early in patients with refractory variceal bleeding once medical treatment and endoscopic sclerotherapy failure, before the clinical condition worsens. Furthermore, admission to specialized centers is mandatory in such a setting and regional protocols are essential to be organized effectively. This review article discusses initial management and then focuses on the specific role of TIPS as a primary therapy to control acute variceal hemorrhage, particularly as a rescue therapy following failure of endoscopic approaches.